In-vivo dark-field and phase-contrast x-ray imaging - Bech, Martin; Tapfer, A.; Velroyen, A.; Yaroshenko, A.; Pauwels, B.; Hostens, J.; Bruyndonckx, P.; Sasov, A.; Pfeiffer, F. (Scientific Reports, 2013)
Novel radiography approaches based on the wave nature of x-rays when propagating through matter have a great potential for improved future x-ray diagnostics in the clinics. Here, we present a significant milestone in this imaging method: in-vivo multi-contrast x-ray imaging of a mouse using a compact scanner. Of particular interest is the enhanced contrast in regions related to the respiratory system, indicating a possible application in diagnosis of lung diseases (e.g. emphysema).
CRIS-Team Scopus Importer:2023-03-08